Listening to young lives at work in Vietnam: third call - Duc, LT; Hittmeyer, A; Favara, M; Porter, C; Scott, D (Young Lives, 2021)
This brief report provides headline findings from the third call in Young Lives at Work's COVID-19 Phone Survey in Vietnam. The young people in our study were contacted by phone between November and December to find out about the continuing impact of the pandemic on their health, well-being, food security, education and work.